2010
DOI: 10.1016/j.neulet.2010.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthesis in brain and astrocytes is inhibited by chronic lithium treatment

Abstract: Lithium is a drug widely used to treat bipolar disorder. It has been shown to inhibit the total activity of phosphoglucomutase (PGM) from rat brains. In this work, we show that lithium inhibits in vitro PGM activity in the cortex, hippocampus, striatum, brainstem and cerebellum. As a compensatory effect, chronic lithium treatment of Wistar rats for 6 weeks caused a 1.6-fold upregulation of cortex PGM activity. No difference was observed in the other areas tested. Another effect of chronic lithium administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In addition, we found that the Ser641phosphorylated form of GS, which is another PP1 substrate (Delibegovic et al, 2003;Suzuki et al, 2001), accumulated in PDMPtreated cells, suggesting that GS was not dephosphorylated under these conditions. Moreover, similar conclusions were drawn by others to explain the lack of GS dephosphorylation they observed when GSK3β was inhibited by the well-known GSK3 inhibitor lithium chloride (LiCl) in cultured astrocytes and L6 myocytes, respectively (Choi and Sung, 2000;de Almeida Souza et al, 2010). Together, our results in conjunction with the data from the literature suggest that in our conditions, both pGSK3βSer9 and pGSSer641 remained elevated after PDMP treatment because both enantiomers reduced the long-chain ceramide species production, which in turn blocked the stimulation of PP1 activity, resulting in a lesser dephosphorylation of GSK3β and GS.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, we found that the Ser641phosphorylated form of GS, which is another PP1 substrate (Delibegovic et al, 2003;Suzuki et al, 2001), accumulated in PDMPtreated cells, suggesting that GS was not dephosphorylated under these conditions. Moreover, similar conclusions were drawn by others to explain the lack of GS dephosphorylation they observed when GSK3β was inhibited by the well-known GSK3 inhibitor lithium chloride (LiCl) in cultured astrocytes and L6 myocytes, respectively (Choi and Sung, 2000;de Almeida Souza et al, 2010). Together, our results in conjunction with the data from the literature suggest that in our conditions, both pGSK3βSer9 and pGSSer641 remained elevated after PDMP treatment because both enantiomers reduced the long-chain ceramide species production, which in turn blocked the stimulation of PP1 activity, resulting in a lesser dephosphorylation of GSK3β and GS.…”
Section: Discussionsupporting
confidence: 72%
“…De Almeida Souza et al, showed that Lithium therapy led to a marked decrease in glycogen content in whole brain. Glycogen metabolism might be implicated in the pathogenesis of bipolar disorder and its diminished synthesis by Lithium can be relevant to treated patients (20). Our study showed that white matter volume in Lithium treated group decreased compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ATP, other important energy substrates, for example, lactate produced by glucose metabolism are used by neurons as an additional energy substrate when metabolic activity is high [148,149]. Glucose carbon can be included in lipids [150], proteins [151], and glycogen [152] and is also a precursor of some neurotransmitters such as γ-aminobutyric acid, GABA [153], glutamate [154], and acetylcholine [155] as well as nicotinamide adenine dinucleotide phosphate reduced (NADPH) essential for maintaining brain antioxidant capacity [156].…”
Section: Brain Energy Crisis and Aβ Accumulation: Cause Or Consequencementioning
confidence: 99%